Механизм реализации стратегии повышения конкурентоспособности организации - Гринченко, Николай Петрович; Лобач, Елена Владимировна; Гринченко, Марина Анатольевна (НТУ "ХПИ", 2017)
В работе представлен механизм повышения конкурентоспособности организации, с помощью которого осуществляется усовершенствование структуры организации, а именно обосновывается включение в структуру организации службы стратегического маркетинга, которая позволит оптимизировать информационные потоки для разработки управленческих решений стратегического менеджмента. Выделены основные принципы управления конкурентоспособностью продукции организации. Предлагается структура механизма реализации стратегии повышения конкурентоспособности организации, которая позволит эффективно формировать стратегические управленческие решения.

The mechanism of the organizational competitiveness increase, which is employed to enhance the organizational structure, has been performed in the research. The principles ensuring the product competitiveness have been pointed out. The involvement into the strategic marketing service organizational structure which aims to optimize the information flows for the development of the managerial decisions has been proved. The generalized structure of strategic marketing services, focused on medium-sized and large enterprises has been proposed. The proposed strategic marketing service develops strategic standards for all production parameters on the first stage of organizational product life cycle. Employing the innovation management methods, it prepares the exclusive values for all production parameters to turn them into an organizational competitiveness according to the following scheme: exclusive value, competitive advantages of products, competitiveness of products and organization competitiveness. Strategic Marketing Service together with top managers performs: the strategic vision and organization mission development, the tree of long-term objectives development, the strategy of the organization competitiveness improvement development, projects formation, control and implementation. The Strategic Marketing Service Management is based on the strategic management functions implementation while performing the strategy of organizational competitiveness increase. The mechanism structure of the strategy of organizational competitiveness increase that will effectively perform the strategic management decisions and convert the exclusive values into the organizational competitiveness has been proposed.
The mechanism for implementing the strategy of competitiveness increase of the organization
Keywords: конкурентоспособность; организация; принципы; стратегический маркетинг; competitiveness; organization; principles; strategic marketing; strategy of competitiveness growth